In the name of the national interests: Foreign policy of Saudi Arabia after the Arab Spring - G. G. Kosach (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The paper examines the evolution of Saudi Arabia’s foreign policy in the context of wider changes in the Middle East and in the Arab world triggered by the Arab Spring. The author argues that during this decade the Kingdom’s foreign policy has witnessed a fundamental transformation: the very essence of the Saudi foreign policy course has changed signiﬁ cantly as the political es-tablishment has substantially revised its approaches to the country’s role in the region and in the world. Before 2011, Saudi Arabia — the land of the ‘Two Holy Mosques’ — positioned itself as a representative of the international Muslim community and in pursuing its foreign policy relied primarily on the religious authority and ﬁ nancial capabilities. However, according to Saudi Arabia’s leaders, the Arab Spring has plunged the region into chaos and has bolstered the inﬂ uence of various extremist groups and movements, which required a signiﬁ cant adjustment of traditional political approaches. Saudi Arabia, more explicit than ever before, has declared itself as a nation state, as a regional leader possessing its own interests beyond the abstract ‘Muslim Ummah’. However, the author stresses that these new political ambitions do not imply a complete break with the previous practice. For example, the containment of Iran not only remains the cornerstone of Saudi Arabia’s foreign policy, but has become even more severe. The paper shows that it is this opposition to Iran, which is now justiﬁ ed on the basis of protecting the national interests, that predetermines the nature and the speciﬁ c content of contemporary Saudi Arabia’s foreign policy including interaction with the Gulf Cooperation Council (GCC), approaches towards the solution of the Israeli-Palestinian conﬂ ict, combating terrorism, and relations with the United States. In that regard, the transformation of Saudi Arabia’s foreign policy has, on the one hand, opened up new opportunities for strengthening the Kingdom’s interaction with Israel, but, at the same time, has increased tensions within the framework of strategic partnership with the United States. The author concludes that currently Saudi Arabia is facing a challenge of diversifying its foreign policy in order to increase its international proﬁ le and political subjectivity.